Isobavachalcone From Cullen corylifolium Presents Significant Antibacterial Activity Against Clostridium difficile Through Disruption of the Cell Membrane - Liu, Xi-Wang; Yang, Ya-Jun; Qin, Zhe; Li, Shi-Hong; Bai, Li-Xia; Ge, Wen-Bo; Li, Jian-Yong (Frontiers in Pharmacology, 2022)
Overview：That Clostridium difficile infection (CDI) caused by Clostridium difficile was widely reported in human and animals around the world over the past decades. The high relapse rate and increasing drug resistance of CDI make the discovery of new agents against C. difficile fairly urgent. This study amied to investigate the antibacterial activity against C. difficile of traditional Chinese herb medicine PF and identificate the active components of the herb. Methods：Phenolic etracts of PF was prepared routinely and the content of major flavonoids was determined by High Performance Liquid Chromatography (HPLC). The antibacterial activitiesof PF etracts and major components was determined by in vitro experiments. Substaincially, the influence of major components on cell membrane was investigated. The therapeutic efficacy of IBCL was evaluated on mice model. Fianlly, cytotoxicity of the etract and compounds on Caco-2 cell line was assessed by CCK-8 kit. Results：PF extracts was found to be active against C. difficile with MIC value of 8 μg/mL. As the major components of PFPE, IBCL was the most active compounds against C. difficile. The MIC values of IBCL and 4MBCLwere 4 μg/mL and 4 μg/mL respectively. Meanwhile, PFPE, IBCL and 4MBCL show rapid bactericidal effect against C. difficilein 1 hour, which was unique compared to traditional antibiotic vancomycin. Mechanism studies revealed that IBCL can disrupt the cell membrane integrity, which may lead to the death of bacteria. IBCL can effectively alleviate the symptoms of CDI on mice as well as reduce death rate, which display significant efficacy compared to vancomycin. At last, PFPE was found to be little cytotoxic against Caco-2 cell and the cytotoxicity of IBCL was moderate. Conclusion：As the major conponents of PF and PFPE, IBCL show significant antibacterial activity against C. difficile in vitro. IBCL may rapidly kill the bacteria through interrupting cell membrane integrity. Although the cytotoxicity was moderate, IBCL can protect mice from weight loss and death cause by CDI, which was proved to be a promising lead compound for CDI control.